The Efficacy of Green Tea Chewing Gum on Gingival Inflammation - Behfarnia, Parichehr (J Dent (Shiraz), 2016)
STATEMENT OF THE PROBLEM: According to previous studies, the components of green tea extracts can inhibit the growth of a wide range of gram-pos-itive and -negative bacterial species and might be useful in controlling oral infections. PURPOSE: The aim of this study was to determine the effect of green tea chewing gum on the rate of plaque and gingival inflammation in subjects with gingivitis. MATERIALS AND METHOD: In this double-blind randomize controlled clinical trial, 45 patients with generalized marginal gingivitis were selected and divided into two groups of green tea (23) and placebo (22) chewing gum. The patients chewed two gums for 15 minutes daily for three weeks. Sulcus bleeding index (SBI) and approximal plaque index (API) were studied at the baseline, 7 and 21 days later. Saliva sampling was conducted before and after 21 days for evaluation of IL-1β. The results were analyzed and compared by using repeated measures ANOVA, paired t test, and independent two-sample t test (α=0.05). RESULT: The results showed that chewing gum significantly affected the SBI and API (p< 0.001). Paired t test showed that the two groups were significantly different regarding the mean changes of SBI and API at different periods of 1-7, 1-21, and 7-21 (p< 0.001). Concerning IL-1β, the repeated measures ANOVA revealed that the effect of chewing gum was significant (p<0.001). Moreover, paired t-test represented no significant difference between the mean changes of IL-1β within 1-21 day (p= 0.086). CONCLUSION: The green tea chewing gum improved the SBI and API and effectively reduced the level of IL-1β.